Էթնիկ գործընթացները Հյուսիսարևելյան Այսրկովկասում (XVIII դարի երկրորդ կես) - Գ. Ժ. Մխիթարյան (ՀՀ ԳԱԱ հրատ.)
С древнейших времен территория Северо-Восточного Закавказья претерпела этнические изменения. В результате этнических передвижений с севера на юг и с юга на север во второй половине XVIII в. его площадь была заселена различными этническими группами. Кроме коренного населения на территории исторической Албании (Алуанк) жили армяне, персы, евреи и различные тюркоязычные кочевые племена. Since ancient times, North-Eastern Transcaucasia has undergone ethnic transformations. Hence, in the second half of the 18th century, its area was populated by groups of various ethnic units. Besides the native nations, Armenians, Persians and Turkic-language nomadic tribes inhabited the region called Aluank (Albania) in the second half of the 18th century. The paper reveals the ethno-political affiliation of the region's Turkish nomadic tribes ''Tatars'' in the second half of the 18th century.
Keywords: History; Geography; Anthropology; Recreation; D History; GEC Ethnic Groups and Races